2007
DOI: 10.1186/1471-2180-7-40
|View full text |Cite
|
Sign up to set email alerts
|

Purification and preliminary crystallization of alanine racemase from Streptococcus pneumoniae

Abstract: Background: Over the past fifteen years, antibiotic resistance in the Gram-positive opportunistic human pathogen Streptococcus pneumoniae has significantly increased. Clinical isolates from patients with community-acquired pneumonia or otitis media often display resistance to two or more antibiotics. Given the need for new therapeutics, we intend to investigate enzymes of cell wall biosynthesis as novel drug targets. Alanine racemase, a ubiquitous enzyme among bacteria and absent in humans, provides the essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
(30 reference statements)
2
22
0
Order By: Relevance
“…A lysine residue connected to the PLP cofactor by an internal aldimine bond acts as a base for the conversion of D-alanine to L-alanine while a nearby tyrosine from the second monomer acts as a base for the abstraction of a hydrogen from L-alanine [5]. According to the generally accepted mechanism, alanine racemase reaction is proposed to proceed in four steps: (1) transaldimination between Lys 39 bound with PLP (I) and the α-amino group of L-alanine to produce an external aldimine II; (2) abstraction of the α-hydrogen from L-alanine to produce a resonance-stabilized quinonoid intermediate III; (3) reprotonation at the α-carbon of the quinonoid intermediate III on the side opposite to that where the α-hydrogen was abstracted; (4) the second transaldimination between IV and Lys 39 to release D-alanine [6]. In the third step, D-amino acid aminotransferase (DAT) catalyzes transamination between α-ketoglutaric acid and D-alanine to produce D-glutamic acid and pyruvic acid [7][8][9].…”
mentioning
confidence: 99%
“…A lysine residue connected to the PLP cofactor by an internal aldimine bond acts as a base for the conversion of D-alanine to L-alanine while a nearby tyrosine from the second monomer acts as a base for the abstraction of a hydrogen from L-alanine [5]. According to the generally accepted mechanism, alanine racemase reaction is proposed to proceed in four steps: (1) transaldimination between Lys 39 bound with PLP (I) and the α-amino group of L-alanine to produce an external aldimine II; (2) abstraction of the α-hydrogen from L-alanine to produce a resonance-stabilized quinonoid intermediate III; (3) reprotonation at the α-carbon of the quinonoid intermediate III on the side opposite to that where the α-hydrogen was abstracted; (4) the second transaldimination between IV and Lys 39 to release D-alanine [6]. In the third step, D-amino acid aminotransferase (DAT) catalyzes transamination between α-ketoglutaric acid and D-alanine to produce D-glutamic acid and pyruvic acid [7][8][9].…”
mentioning
confidence: 99%
“…Bacteria contain either one or two alanine racemase genes. In species with two genes, one is constitutively expressed and anabolic, while the other is inducible and catabolic (25)(26)(27). These genes supply the D-alanine needed for cell wall biosynthesis, and knockout studies with several of these bacteria have established that the alanine racemase enzyme is essential for growth in the absence of exogenous D-alanine (9,12,18,24,33,34).…”
mentioning
confidence: 99%
“…The monomeric enzymes are those from crayfish (10), marine gastropod Cellana grata (11), and Thermus thermophilus (12). The homodimeric enzymes are those from Bacillus psychrosaccharolyticus (13), Penaeus monodon (8) and Streptococcus pneumoniae (14). Recent progress in crystal structural analyses has demonstrated that all analyzed alanine racemases from Geobacillus stearothermophilus (15), Pseudomonas aeruginosa (16), Streptomyces lavendulae (17), and Mycobacterium tuberculosis (18) are in dimeric form.…”
mentioning
confidence: 99%